Healing Field: Using Alternating Electric Fields to Prevent Cytokine Storm by Suppressing Clonal Expansion of the Activated Lymphocytes in the Blood Sample of the COVID-19 Patients - Abadijoo, Hamed; Khayamian, Mohammad Ali; Faramarzpour, Mahsa; Ghaderinia, Mohammadreza; Simaee, Hossein; Shalileh, Shahriar; Yazdanparast, Seyed Mojtaba; Ghabraie, Bahman; Makarem, Jalil; Sarrami-Forooshani, Ramin; Abdolahad, Mohammad (Frontiers in Bioengineering and Biotechnology, 2022)
In the case of the COVID-19 early diagnosis, numerous tech innovations have been introduced and many of them are currently employed around the world. But, all of the medical procedures for the treatment of this disease, up to now, are just limited to chemical drugs. All of the scientists believe that the major challenge toward the mortality of the COVID-19 patients is the out-of-control immune system activation and the subsequent cytokine production. During this process, the adaptive immune system is highly activated, and many of the lymphocytes start to clonally expand, and hence many cytokines are also released. So, any attempt to harness this cytokine storm and calm down the immune outrage is appreciated. While the battleground for the immune hyperactivation is the lung ambient of the infected patients, the only medical treatment for suppression of the hypercytokinemia is based on the immunosuppressor drugs that systemically dampen the immunity with many unavoidable side effects. Here, we applied the alternating electric field to suppress the expansion of the highly activated lymphocytes and by reducing the number of the renewed cells, the produced cytokines were also decreased. Applying this method to the blood of the COVID-19 patients in-vitro showed 33% reduction in the average concentration of the three main cytokines after 4 days of stimulation. This method could carefully be utilized to locally suppress the hyperactivated immune cells in the lung of the COVID-19 patients without any need for systemic suppression of the immune system by the chemical drugs.